Pariwisata Digital Pada Objek Wisata Dengan Aplikasi - I Gusti Ketut Indra Pranata Darma (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2020)
Current technological advances are inevitable we must follow along with the development of such a rapid era. Starting from the 1.0 era until now that is being launched is industry 5.0. Moreover, the existence of the Covid-19 Pandemic that is currently happening is quite hitting many industries ranging from garment, automotive, trade to tourism. Since February 2020 there has been a decline in tourist arrivals due to restrictions on visits from various countries. Bali tourism also felt the impact and began to have an impact on the lack of visits to various tourist attractions. This research will try to raise the design of a tourism digitally by using a Zoneminder application so that tourism objects can be seen directly at that moment. The concept of the design using Zoneminder is expected to be able to present new experiences in traveling for tourists and still help managers of attractions to remain creative and get donations in presenting attractions in the form of direct donations or advertising. Keywords: Tourism; Zoneminder; Covid